Characteristics of an Iron-Reducing, Moderately Acidophilic Actinobacterium Isolated from Pyritic Mine Waste, and Its Potential Role in Mitigating Mineral Dissolution in Mineral Tailings Deposits - Nancucheo, Ivan (Microorganisms, 2020)
Reactive pyritic mine tailings can be populated by chemolithotrophic prokaryotes that enhance the solubilities of many metals, though iron-reducing heterotrophic microorganisms can inhibit the environmental risk posed by tailings by promoting processes that are the reverse of those carried out by pyrite-oxidising autotrophic bacteria. A strain (IT2) of Curtobacterium ammoniigenes, a bacterium not previously identified as being associated with acidic mine wastes, was isolated from pyritic mine tailings and partially characterized. Strain IT2 was able to reduce ferric iron under anaerobic conditions, but was not found to catalyse the oxidation of ferrous iron or elemental (zero-valent) sulfur, and was an obligate heterotrophic. It metabolized monosaccharides and required small amounts of yeast extract for growth. Isolate IT2 is a mesophilic bacterium, with a temperature growth optimum of 30 °C and is moderately acidophilic, growing optimally at pH 4.0 and between pH 2.7 and 5.0. The isolate tolerated elevated concentrations of many transition metals, and was able to grow in the cell-free spent medium of the acidophilic autotroph Acidithiobacillus ferrooxidans, supporting the hypothesis that it can proliferate in acidic mine tailings. Its potential role in mitigating the production of acidic, metal-rich drainage waters from mine wastes is discussed.